Characterization of a novel roseophage and the morphological and transcriptional response of the sponge symbiont Ruegeria AU67 to infection. (29th March 2021) - Baum, Lisa; Nguyen, Mary T. H. D.; Jia, Yunke; Biazik, Joanna; Thomas, Torsten
Summary: Sponges have recently been recognized to contain complex communities of bacteriophages; however, little is known about how they interact with their bacterial hosts. Here, we isolated a novel phage, called Ruegeria phage Tedan, and characterized its impact on the bacterial sponge symbiont Ruegeria AU67 on a morphological and molecular level. Phage Tedan was structurally, genomically and phylogenetically characterized to be affiliated with the genus Xiamenvirus of the family Siphoviridae . Through microscopic observations and transcriptomic analysis, we show that phage Tedan upon infection induces a process leading to metabolic and morphological changes in its host. These changes would render Ruegeria AU67 better adapted to inhabit the sponge holobiont due to an improved utilization of ecologically relevant energy and carbon sources as well as a potential impediment of phagocytosis by the sponge through cellular enlargement. An increased survival or better growth of the bacterium in the sponge environment will likely benefit the phage reproduction. Our results point towards the possibility that phages from host‐associated environments require, and have thus evolved, different strategies to interact with their host when compared to those phages from free‐living or planktonic environments.